Methods of Using Information Technologies in Teaching Quantities to Primary School Students - Jalilov Muhammadali Abdumutalibovich; Mamirova Mehruzabonu Khurshidbek Qizi (European International Journal of Pedagogics, 2025)
This article discusses the importance of teaching quantities in primary school mathematics lessons, the role of the topic in the development of primary school students, and the advantages and benefits of using modern computer technologies to explain quantities in primary school lessons.